Peran Self-Compassion dalam Menurunkan Tingkat Academic Burnout Pada Mahasiswa Indonesia - Aisyah Hidayah Putri; Auliya Syaf; Itto Nesyia Nasution (Psychopolytan : Jurnal Psikologi, 2025)
Academic burnout is a condition in which a person experiences burnout, cynicism, and a sense of inadequacy in their academic endeavors. Self-compassion is the process by which people understand themselves without judging their pain, shortcomings, or inadequacies while also recognizing that these things are part of life in general. he subjects in this study consisted of 323 students. The sampling technique used was quota sampling. Data collection was carried out through the academic burnout scale which contained 23 items and the self-compassion scale which contained 22 items. Data analysis was conducted using the Product Moment Correlation technique. Based on the results of data analysis, there was a significant negative relationship between self-compassion and academic burnout in students with a significance value of p = .000 and a correlation coefficient of r = –.587. This indicates a moderate-strength relationship between the two variables, and therefore, the hypothesis in this study is accepted.. The results of this study show that students are able to manage academic burnout through the enhancement of self-compassion, in line with the implications provided where self-compassion plays a role in improving self-management, positive mindset, and preventing academic burnout among students.